The role of edible cities supporting sustainability transformation – A conceptual multi-dimensional framework tested on a case study in Germany - Artmann, Martina; Sartison, Katharina; Vávra, Jan (Elsevier SCI LTD, 2020)
Cities have become major contributors to sustainability problems and, in the meantime, seedbeds for sustainability transformation. Urban nature-based solutions, such as greening strategies that foster urban food production as a cross-cutting issue, promise to have multidimensional benefits for sustainable urban development. However, a conceptual understanding of interlinkages between nature-based solutions and their contribution to sustainability transformation is lacking. The goals of this study are twofold. First, to develop a conceptual model for testing multi-dimensional impacts of urban nature based solutions supporting social-spatial, social-ecological and individual sustainable transformation. The model has been developed based on the concepts of place attachment, human-food connection and pro-environmental food behaviour. Second, the conceptual model is applied to the example of edible cities. Edible cities can be considered an innovative nature-based solution that provides multiple cobenefits by offering (free) food for urban residents in public spaces. A Principal Component Analysis of a survey among residents of Andernach (N = 380), one of the first edible cities in Germany revealed, in contrast to the conceptual three-dimensional model, a four-dimensional model with high construct validity and reliability. The model comprises a) place attachment, b) experiential and c) material humanfood connection as well as d) pro-environmental food consumption. Items of internal emotional and philosophical human-food connection included within the pro-environmental food consumption scale suggested their important role in fostering sustainability. Results suggest that the edible city can be considered a strategy for increasing urban attractiveness and place identity, supporting social bonding and experiential human-food connection by using the edible areas for nature observation and recreation. However, although the residents are well informed about the edible city concept, most residents are not actively involved and rarely use the food provided by the edible city. Thus, they also could not answer questions related to cognitive human-food connection such as estimating the food’s taste and health quality. To strengthen material and cognitive human-food connection, policy implications of the results propose the implementation of accompanying information and participation activities. By linking naturebased solutions with sustainability transformation, this study provides conceptual and practical implications for the multidimensional benefits of innovative urban greening strategies such as edible cities.
Keywords: Human-nature connection; Place attachment; Pro-environmental food behavior; Urban living quality; Urban gardening; Urban agriculture